The role of the nurse in the face of snakebite victims in pre-hospital and intra-hospital accidents - Santos, Rafael de Carvalho dos; Santos, Daniel de Oliveira dos; Silva, Maria Fernanda Albuquerque Ferreira da; Silva, Maylla Monteiro da (Seven Editora, 2023)
Objective: to expose the incidence of ophidian accidents, as well as the emergency, pre-hospital and in-hospital actions. Method: The search was conducted in the following databases: Scientific Electronic Library Online (SciELo), Latin American and Caribbean Literature on Health Sciences (LILACS) and Google Scholar. Results: The sample of the present work encompasses 11 articles with common objectives, such objectives are constituted in the intention of identifying the possible contributions of the professional in the scope of nursing for patients victims of ophidian accidents, where it was exposed that this assumes a role of great relevance in the care and assistance. Final considerations: it was found that nurses in cases of ophidian accidents must tranquilize the patient, keep the site of the bite elevated, keep the individual lying down, perform a physical examination and analyze vital functions. Serotherapy, with infusion of the antidote serum, is the most effective treatment in these cases, and the nurse must also constantly monitor the patient and administer medication. DOI:https://doi.org/10.56238/alookdevelopv1-197